The Role of the Rho/ROCK Pathway in Ang II and TGF-β1-Induced Atrial Remodeling - Liu, Li-Juan; Yao, Feng-Juan; Lu, Gui-Hua; Xu, Cheng-Gui; Xu, Zhe; Tang, Kai; Cheng, Yun-Jiu; Gao, Xiu-Ren; Wu, Su-Hua (PloS one, 2016)
To study the role of the Rho/ROCK pathway in Ang II and TGF-β1-induced atrial remodeling. A canine atrial fibrillation (AF) model was established by rapid atrial pacing (RAP) of the left atrium. The roles of TGF-β1, the RhoA/ROCK signaling pathway and connective tissue growth factor (CTGF) in atrial remodeling were studied via both in vitro and in vivo experiments. Each of the dogs that received RAP developed persistent AF within 4 weeks. The mRNA expression levels of TGF-β1 (1.32±0.38), Collagen-I(1.33±0.91), CTGF(5.83±3.71), RhoA(1.23±0.57) and ROCK-1 (1.02±0.27) in the left atrium were significantly increased following 4 weeks of RAP. Angiotensin II (Ang II) induced the proliferation of atrial fibroblasts and up-regulated the expression of both CTGF and ROCK-1 in a dose-dependent manner. Simvastatin and Y27632 reversed Ang II-induced CFs proliferation, as well as ROCK-1(0.89±0.05 and 1.27±0.03, respectively) and CTGF (0.87±0.04 and 0.91±0.02, respectively) expression. The expression mRNA of ROCK-1(1.74±0.13) and CTGF (2.28±0.11) can upregulated by TGF-β1, and down-regulated by Simvastatin (1.22±0.03 vs 2.27±0.11), Y27632 (1.01±0.04 vs 1.64±0.03), Los (1.04±0.11 vs 1.26±0.05), respectively. Losartan and Simvastatin attenuated the effects of TGF-β1, inhibited RhoA activity as opposed to RhoA protein expression. Y27632 had no effect on either the expression or the activity of RhoA. The increased expression of profibrotic factors (CTGF, ROCK1 and Smad2/3) played an important role in our RAP-induced AF model. Increased atrial profibrotic factors involve the activation of either the TGF-β1/RhoA/ROCK-1 or the TGF-β1/Smad2/3 signaling pathway.